AN EVALUATION OF THE FUNDAMENTAL FACTORS INFLUENCING THE CHARACTERISTICS OF MYCELIUM-BASED MATERIALS: A REVIEW. - Karaman, Maja (Journal on Processing and Energy in Agriculture, 2024)
The mycelium-based materials (MBMs) are produced by growing the vegetative part of the mushroom-forming fungi - from Dikarya group: phylum Basidiomycota and Ascomycota, on different organic substrates, mostly due to containing important mycelium characteristics: septa and anastomosis. Moreover, function of these composites can be further tuned by controlling the species of fungus, the growing conditions, and the processing methods to meet a specific mechanical requirement in their further applications. The material formed after full colonization of the substrate, needs to be exposed to dry heating in order to remove the moisture content and to inactivate the mycelium, giving us the lightweight, and biodegradable material with great potential to replace fossil-based and synthetic materials such as polyurethane and polystyrene. Their low carbon footprint, low energy and processing cost, biodegradability, low heat conductivity, high acoustic absorption, and fire safety qualities were some of the main characteristics that encouraged the use of mycelium based composites (MBCs)in the construction and building sector, especially as paneling, insulation, and furniture materials. Since mycelium products are quite new and there is limited industry peer-reviewed testing data available, there is a need for standardized mechanical properties, universal testing requirements and published standards (ISO, ASTM) to ensure that qualification and testing programs can be developed to support the manufacture and use of MBCs.